2021
DOI: 10.3389/fonc.2021.690777
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant Radiotherapy After Minimally Invasive Surgery in Patients With Stage IA1-IIA1 Cervical Cancer

Abstract: To estimate whether adjuvant radiotherapy is necessary for patients with stage IA1-IIA1 cervical cancer after laparoscopic hysterectomy, 221 patients were retrospectively analyzed. Sixty-two of them were treated with laparoscopic hysterectomy and adjuvant radiotherapy (group A), 115 underwent open surgery (group B) and 44 received laparoscopic hysterectomy alone (group C). Results showed that the 3-year local recurrence-free survival (LRFS) rates of group A, B and C were 98.4%, 97.4% and 86.4%, respectively. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
0
1
0
Order By: Relevance
“…The results may differ due to several factors. Firstly, the surgical-related factors that result in poor patient survival, such as utilizing a uterine manipulator, the effect of insufflation gas (CO 2 ), and the degree of resection, can be improved by postoperative RT or CRT [18][19][20]. Secondly, many studies indicated that a longer adjuvant RT wait-time after RH result in poorer oncologic outcome in early-stage CC [21,22].…”
Section: Discussionmentioning
confidence: 99%
“…The results may differ due to several factors. Firstly, the surgical-related factors that result in poor patient survival, such as utilizing a uterine manipulator, the effect of insufflation gas (CO 2 ), and the degree of resection, can be improved by postoperative RT or CRT [18][19][20]. Secondly, many studies indicated that a longer adjuvant RT wait-time after RH result in poorer oncologic outcome in early-stage CC [21,22].…”
Section: Discussionmentioning
confidence: 99%
“…They observed a statistically significant increase in 3-year local recurrence-free survival (LRFS) in patients who received adjuvant RT compared to surgery alone. [18] Solis et al analyzed the data of 28 patients who underwent adjuvant small pelvic field radiotherapy without brachytherapy or chemotherapy for intermediate risk. They reported OS, DFS and LRFS as 100%, 82% and 86% respectively at a median follow-up of 41 months.…”
Section: Rotman Et Al Investigated the Role Of Postoperative Rt In Amentioning
confidence: 99%